Handbook on innovations in learning - Murphy, Marilyn; Redding, Sam; Twyman, Janet (Emerald Publishing Limited : Information Age Publishing Inc., 2014)
An innovation in learning improves upon the implementation of the standard practice or introduces a new practice, thus achieving greater learning outcomes. The Handbook on Innovations in Learning, developed by the Center on Innovations in Learning, presents commissioned chapters describing current best practices of instruction before embarking on descriptions of selected innovative practices which promise better methods of engaging and teaching students. Written by a diverse and talented field of experts, chapters in the Handbook seek to facilitate the adoption of the innovative practices they describe by suggesting implementation policies and procedures to leaders of state and local education agencies.